The DSF quorum sensing system controls the positive influence of Stenotrophomonas maltophilia on plants. - Peyman Alavi (Public Library of Science (PLoS), 2013)
The interaction of the Gram-negative bacterium Stenotrophomonas maltophilia with eukaryotes can improve overall plant growth and health, but can also cause opportunistic infections in humans. While the quorum sensing molecule DSF (diffusible signal factor) is responsible for the regulation of phenotypes in pathogenic Stenotrophomonas, up until now, no beneficial effects were reported to be controlled by it. Our objective was to study the function of DSF in the plant growth promoting model strain S. maltophilia R551-3 using functional and transcriptomic analyses. For this purpose, we compared the wild-type strain with a mutant deficient in the rpfF (regulation of pathogenicity factors) gene that is essential for the synthesis of DSF. Oilseed rape seeds treated with the wild-type strain showed a statistically significant increase in germination rate compared with those treated with the rpfF mutant. Similarly, the wild-type strain exhibited better plant growth promotion and a greater efficiency in colonizing oilseed rape compared to the mutant strain. Moreover, only the wild-type was capable of forming structured cell aggregates both in vitro and in the rhizosphere, a characteristic mediated by DSF. Gene transcription analyses showed that numerous genes known to play a role in plant colonization (e.g. chemotaxis, cell motility, biofilm formation, multidrug efflux pumps) are controlled by the rpf/DSF system in S. maltophilia. In addition, we detected new potential functions of spermidine, primarily for both growth promotion and stress protection. Overall, our results showed a correspondence between the regulation of DSF and the positive interaction effect with the plant host.